Pengaruh Perputaran Kas, Perputaran Piutang Dan Perputaran Persediaan Terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Hidayati, Devita; Astuti, Puji; Widiawati, Hestin Sri (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Company profitability is an indicator that is often used by the public, especially investors, to measure company performance achievements. One factor that can influence profitability is efficiency in managing current assets such as cash, receivables and inventory. This efficiency can be measured through cash turnover ratios, receivable turnover and inventory turnover. This research aims to analyze the influence of cash turnover, receivables turnover and inventory turnover on the profitability of food and beverage sub-sector companies listed on the IDX for the 2021 - 2023 period, totaling 95 companies. The sampling technique used was purposive sampling and a sample of 21 food and beverage sub-sector companies was obtained as samples for data collection which was then analyzed using the classic assumption test, multiple linear regression analysis, t test, F test and determination test. The results of the analysis show that cash turnover, accounts receivable turnover and inventory turnover have a significant effect on company profitability. Based on the results of the research, it is hoped that it can be used as consideration for companies to pay attention to the current asset ratio in order to increase productivity and become reference material for future researchers in taking up similar research topics.